Detection of Salmonella spp., Escherichia coli, and Listeria monocytogenes in Tuna by Multiplex PCR - Kristina Natalia; Mariana Wahjudi; Tjie Kok (Department of Aquaculture, 2022)
Fishery products are types of commodity with various levels of development including the addition of food additives. They are very susceptible to patogenic microbial contamination hence they can cause food poisoning and cause disease outbreaks in consumers. In this study, tuna fish spiked with Salmonella spp., Escherichia coli, and Listeria monocytogenes bacteria is examined for the bacteria contamination. The examination of these patogenic bacteria is carried out using multiplex PCR (mPCR), a modern technique developed to detect target DNAs of bacteria simultaneously. The results of the examination are compared to biochemical test for sensitivity and time-efficiency. Based on the results obtained, mPCR method is ±1250-fold more sensitive and ±80-fold more time-efficient than the biochemical tests. Therefore, mPCR method could be recommended to be used as a tool for detection of bacteria in fishery products.